A model for the vibrator–ground coupling vibration and the dynamic responses under excitation of sweep signal. Issue 8 (June 2019) - Li, Gang; Huang, Zhi-Qiang; Lian, Zhang-Hua; Hao, Lei
To analyze the behavior of the vibrator–ground coupling vibration, a model containing equivalent dynamic stiffness and equivalent dynamic damping to describe the interaction between the vibrator and the ground is established based on half-space theory. According to load cell test, this model shows a good agreement with the experimental data. Dynamic responses of the structure are analyzed on displacement, velocity, acceleration, and ground force. Results show that the stroke and pump displacement are main constraints that limit the bandwidth of vibrator toward low frequency, and the stroke of conventional vibrator is not long enough to achieve lower frequency. Analysis of velocity response indicates that with the increase of frequency, a larger mass results in a lower velocity under external force. The influence of the ground acting on the baseplate is limited, and the acceleration of the baseplate is determined by its own mass beyond 80 Hz. Analysis of ground force shows that the response of the structure can be divided into three stages. The reaction mass, the baseplate, and the ground play different roles in dominating the ground force at different frequency bands.